Slip transition of rock fractures due to chemical corrosion - Mei, Cheng (2022)
Chemical corrosion of rock masses commonly exists in natural environment (e.g., rock masses immersed in acidic groundwater) and in rock engineering practice (e.g., acid fluid injection in unconventional reservoirs). Rock fractures as the primary paths for fluid flow are susceptible to the chemical treatment, which may lead to geologic hazards (e.g., induced landslides and earthquakes). Here we show the transitional behaviors of rock fractures between stick-slip and stable sliding due to the chemical corrosion, which is characterized by a sequence of fast rupture followed by one or more slow ruptures. The chemical corrosion also modifies the frictional properties of rock fractures, in terms of friction rate parameters, characteristic weakening distance, stiffness ratio, and frictional property ratio. Our results indicate that the chemical corrosion essentially reduces the critical stiffness of the fracture and makes it approach the stiffness of the loading system, resulting in the occurrence of slip transition. The slip transition is strongly influenced by treatment duration and shear process, and the real area of contact density is a physical control linking fracture surface topography and frictional responses, such as AE energy and shear stress drop. The understanding of slip transition can improve our ability to interpret the seismic data and to predict the slip behaviors.